Development Gross Pollutant Management Strategies Knowledge Database using ArcGIS - H. Haron, S.; F. M. Said, N.; M. Sidek Basri, L.; Basri, H.; M. Zahari, N.; C. Muda, Z.; M. Dom, N.; Ahmad, R. (International Journal of Engineering and Technology, 2018)
This study aims to suggest an efficient method for the management of gross pollutants. The local data collected will finally become input to Innovative Gross Pollutant Management Strategies Knowledge Database, which will help engineers or local authorities to manage the GPTs efficiently. Furthermore, the knowledge management portal ensures knowledge sharing and the establishment of knowledge bank for Gross Pollutant under Malaysian condition. The developed gross pollutant management strategies knowledge database is able to assist the client during inspection & maintenance data collection using ArcGIS Collector. The data will be uploaded into the web base ARC GIS Online System, enable better management of gross pollutant traps, in term of inspection & maintenance. The result obtained in this study provides information that can help future decision for GPTs installation and maintenance program. Ultimately, the data obtained will assist the engineers and local authorities to implement appropriate strategies for trapping gross pollutants in an urban area, expand the sources for managing gross pollutants in order to rehabilitate the river system and preparing budget allocation for GPTs operation & maintenance.Â Â Â